Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Usaha Dan Energi di Kelas Xi Ma Al-Ikhwan Gotowasi - Nurlete, Yulianti; Lana, Kartini (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2025)
This study aims to improve students’ learning outcomes in physics, particularly on the topic of Work and Energy, through the implementation of the Problem-Based Learning (PBL) model. The research was conducted at MA Al-Ikhwan Gotowasi involving Grade XI students during the odd semester of the 2023/2024 academic year. The study employed a Classroom Action Research (CAR) design following the spiral model of Kemmis and McTaggart, consisting of two cycles, each comprising planning, action, observation, and reflection stages. Data were collected through learning outcome tests and observation sheets that measured teacher and student activities during the learning process. The data were analyzed descriptively to examine improvements in students’ learning outcomes and learning engagement across cycles. The results indicated a significant improvement in students’ learning outcomes after the implementation of the Problem-Based Learning model. In Cycle I, the percentage of students achieving the minimum mastery criterion increased to 57%, while in Cycle II, mastery learning further improved to 76%. In addition, observations revealed enhanced student engagement, collaborative problem-solving skills, and active participation during physics learning activities. These findings suggest that the Problem-Based Learning model is effective in improving students’ learning outcomes and learning engagement in physics, even in educational contexts with limited laboratory facilities. Therefore, PBL can be considered a viable instructional alternative for physics teachers to promote meaningful learning and improve conceptual understanding of abstract physics topics such as Work and Energy.